Diagnostic Efficacy of 24-hr Esophageal pH Monitoring in Patients with Refractory Gastroesophageal Reflux Disease - Gharib, Atoosa (Open Access Maced J Med Sci, 2018)
BACKGROUND: Gastric reflux is one of the most important causes of the referral of patients to the internal clinic, which in some cases causes problems for patients due to resistance to common treatments. Therefore, timely diagnosis and treatment of this group of patients are very important. AIM: The purpose of the present study was to determine the off-proton pump inhibitor (off-PPI) 24 h pH-impedance analyses in patients with refractory gastroesophageal reflux disease (GERD) attending to Taleghani Hospital since 2009 to 2017. METHODS: In this observational descriptive-comparative off-PPI study, 572 patients with refractory GERD who were referred to Taleghani Hospital in Tehran from 2009 to 2017 were selected, and the results of 24 h pH Impedance analysis were then assessed. RESULTS: The results of 24h pH-impedance indicated that 7% of cases belonged to Pure Acid Reflux followed by weakly Acid (1%), non-acid (0.3%), mixed & gas (5.2%), functional (58.4%) and oesophagal hypersensitivity (28%). Furthermore, weakly acid plus acid was also found to be 8% and Weakly Acid + Acid + Non-Acid were determined as 8.3%. CONCLUSIONS: Our findings suggested that nearly more than half of the patients with refractory GERD would have a functional disorder in the 24h pH-impedance analysis.